Use of simulations of mesoscale convective systems to build a convective parameterization scheme - Alexander, G. David, author (Colorado State University. Libraries, 1995)
A method is described for parameterizing thermodynamic forcing by the mesoscale flow branches of mesoscale convective systems (MCSs) in models with resolution too coarse to resolve these flow branches. This thermodynamic portion of the parameterization contains improvements over previous schemes, including a more sophisticated convective driver and inclusion of the vertical distribution of various physical processes obtained through conditional sampling of two cloud-resolving MCS simulations. A convective momentum parameterization has also been included as a separate component of the parameterization scheme. The momentum scheme includes a parameterization of the convective-scale pressure gradient force, and therefore can account for the effect of the mesoscale organization of the convection on the largescale momentum tendencies. The mesoscale parameterization is tied to a version of the Arakawa-Schubert convective parameterization scheme which is modified to employ a prognostic closure. The parameterized Arakawa-Schubert cumulus convection provides condensed water, ice, and water vapor which drives the parameterization for the large-scale effects of mesoscale circulations associated with the convection. In the mesoscale thermodynamic parameterization, det ermining thermodynamic forcing of the large scale depends on knowing the vertically integrated values and the vertical distributions of phase transformation rates and mesoscale eddy fluxes of entropy and water vapor in mesoscale updrafts and downdrafts. The relative magnitudes of these quantities are constrained by assumptions made about the relationships between various quantities in an MCS 's water budget deduced from the cloud-resolving MCS simulations. The MCS simulations include one of a tropical MCS observed during the 1987 Australian monsoon season (EMEX9), and one of a midlatitude MCS observed during a 1985 field experiment in the central Plains of the U.S. (PRE-STORM 23-24 June).
December 1, 1995.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1996.
Keywords: Convective clouds; Atmospheric circulation